Effect of herbicide application on leaf rust development in wheat under artificial epiphytotics - P., JAYPRAKASH1; V.K. VIKAS1, J.KUMAR1*, R.S. CHHOKAR2, RAJBIR YADAV3, M. SIVASAMY1, G.P.SINGH3, JOHN PETER1 (Indian Phytopathology, 2012)
Interference of various herbicides on leaf rust development in wheat has been discussed in this paper since it is a common practice to apply herbicides pendimethalin at pre-emergence as well as 2,4-D and metribuzin at post – emergence stages for achieving an effective weed control as manual uprooting is laborious and uneconomical. Herbicidal treatments showed their effects on the progression of leaf rust in a manner either dependent upon their chemical composition or the method of application. Pendimethalin did not interfere with the leaf rust build up while 2,4-D and metribuzin put a restraint on build up of leaf rust but only temporarily. Leaf rust progression in the plots treated with 2,4-D and metribuzin normalised in the later stages. Hence, there is no harm in applying these herbicides in leaf rust screening plots for easier and more effective weed management as compared to hand weeding. However, application of 2,4-D and metribuzin may not be suitable in experimental plots meant for recording leaf rust response at early growth stages of wheat especially while enumerating the parameters of slow rusting etc. since both these herbicides had static effect on leaf rust build up in the initial stages. Possibility of using 2,4-D and metribuzin for chemical control of leaf rust of wheat based on the principles of systemic acquired resistance is also discussed.